(untitled) (International Journal of Engineering and Computer Science, 2017)
Among all the phases in software development cycle, maintainability forms the key phase. Once the software is engineered, Software maintenance is the most effort and cost consuming part. A quality software must be adaptable to any real time working conditions. In a component-based system, different components are integrated, enrichment/improvement of a component to make it adaptable to prevailing conditions require more cost. This research presents the modeling work and prototyping techniques, which highlights the importance of project quality analysis for perspective maintainability. Here we are proposing a mathematical approach for time computation which is the sum of response time and time for solution generation. For efficient analysis we require high execution speed for handling complex algorithms and huge data volumes. For this we are providing aspect oriented programming techniques which increase the development speed, modularity that outputs quality products